2021
DOI: 10.1002/pros.24227
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of nerve growth factor‐targeting therapy on bladder overactivity in rats with prostatic inflammation

Abstract: Background: The present study examined the effect of liposomes conjugated with antisense oligonucleotide of nerve growth factor (NGF-OND) on local overexpression of NGF and bladder overactivity using rats with prostatic inflammation (PI).Methods: Male Sprague-Dawley rats were divided into three groups: (1) Control group; intact rats, (2) PI-NS group; rats with PI and intravesical instillation of normal saline (NS), (3) PI-OND group; rats with PI and intravesical instillation of NGF-OND.On Day 0, PI was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…It was found that chronic prostatitis excited its afferent nerves and increased transient receptor potential vanilloid1 (TRPV1) channel expression in L6-S1 DRG. It results in afferent neurons hyperexcitability, NGF up-regulation of bladders and prostates, and bladder abnormality [ 60 ]. Furthermore, it was observed in CP/CPPS that NGF was up-regulated, and the parasympathetic function of bladders was activated and sensitized following DRG excitement [ 41 ].…”
Section: Autonomic Nervous System Dysfunction’s Close Relation With C...mentioning
confidence: 99%
“…It was found that chronic prostatitis excited its afferent nerves and increased transient receptor potential vanilloid1 (TRPV1) channel expression in L6-S1 DRG. It results in afferent neurons hyperexcitability, NGF up-regulation of bladders and prostates, and bladder abnormality [ 60 ]. Furthermore, it was observed in CP/CPPS that NGF was up-regulated, and the parasympathetic function of bladders was activated and sensitized following DRG excitement [ 41 ].…”
Section: Autonomic Nervous System Dysfunction’s Close Relation With C...mentioning
confidence: 99%
“…Finally, it has been reported that prostatic inflammation is an important factor of LUTS in patients with BPH and that the degree of prostatic inflammation in BPH specimens is associated with the severity of LUTS [ 154 , 155 ]. Accordingly, animal models of prostatic inflammation induced by chemical irritation in rats or prostatic epithelium-specific deletion of E-cadherin in mice showed that prostatic inflammation-induced bladder overactivity due to prostate-to-bladder pelvic organ cross-sensitization through afferent hyperexcitability, which is mediated at least in part by NGF upregulation in the bladder [ 156 - 159 ]. Thus, local inflammation in the prostate seems to be an important factor inducing male LUTS in BPH patients.…”
Section: Pathological Conditions Underlying Oabmentioning
confidence: 99%
“…Igarashi et al reported that nerve growth factor, locally expressed in the bladder, is an important mediator inducing bladder overactivity with the upregulation of C-fiber afferent markers following 5% formalin-induced prostate inflammation in a rat model. Thus, the cross-sensitization between the prostate and the bladder causes the complexity of CP/CPPS symptoms [ 3 ]. Persistent pain not only leads to physical discomfort but also affects the psychological state and prevents people from working, thus placing a financial burden on patients and society [ 4 ].…”
Section: Introductionmentioning
confidence: 99%